2018
DOI: 10.1038/s41565-018-0181-4
|View full text |Cite
|
Sign up to set email alerts
|

Low-voltage electrostatic modulation of ion diffusion through layered graphene-based nanoporous membranes

Abstract: Ion transport in nanoconfinement differs from that in bulk and has been extensively researched across scientific and engineering disciplines. For many energy and water applications of nanoporous materials, concentration-driven ion diffusion is simultaneously subjected to a local electric field arising from surface charge or an externally applied potential. Due to the uniquely crowded intermolecular forces under severe nanoconfinement (<2 nm), the transport behaviours of ions can be influenced by the interfacia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
201
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(206 citation statements)
references
References 39 publications
5
201
0
Order By: Relevance
“…Although nanopores may only be able to accommodate one or two ionic layers where this overscreening effect could be prevented, the short‐range ion–ion correlation may still affect the transport of ions in nanopores . It has recently been found that ion–ion correlation could also account for the ability of electrostatic modulation of ion diffusion in graphene‐based nanochannels of less than 2 nm …”
Section: Why Nanoconfinement Matters For Solvated Ions?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although nanopores may only be able to accommodate one or two ionic layers where this overscreening effect could be prevented, the short‐range ion–ion correlation may still affect the transport of ions in nanopores . It has recently been found that ion–ion correlation could also account for the ability of electrostatic modulation of ion diffusion in graphene‐based nanochannels of less than 2 nm …”
Section: Why Nanoconfinement Matters For Solvated Ions?mentioning
confidence: 99%
“…Examples of this approach include chemical functionalization and thermal annealing . Additionally, the electrons inside the materials can be modulated by the means of voltage bias or light illumination so that the electrostatic interactions (e.g., Debye screening in EDL) between ions and materials could be indirectly regulated through the coupling of electrons and ions . Examples of materials with such functionality include graphene and MoS 2 , where metal‐semiconductor transition for modulation of electrons could be achieved by controlling the reduction level or phase transition .…”
Section: Desirable Materials Characteristics For Nanoionics Research mentioning
confidence: 99%
“…Surprisingly, two distinct peaks of the counter-ions will be observed with a surface charge density of −0.2882 C m −2 . [150] Generally, diffusion phenomena are mainly divided into two types, namely, the diffusion caused by the concentration gradient and self-diffusion by the heat movement. [146][147][148] This can be explained that one layer of counter-ions is dehydrated and adsorbed onto the negatively charged solid wall under high surface charge density, which forms the inner Helmholtz plane.…”
Section: Ion Distribution and Diffusion In Nanochannelsmentioning
confidence: 99%
“…[17,18] Theasymmetric shapes and charge distributions of nanochannels contribute to the generation of their rectification characteristics. [19] Nanochannels with rectifying characteristics can be roughly divided into two types:h omogeneous structures [20] and heterostructures. [21,22] In general, stimulusresponsive gating, such as pH gating [23][24][25] and light-responsive gating, [26][27][28] can be achieved by the functional modification of the inner surface of the nanochannel.…”
Section: Introductionmentioning
confidence: 99%